Parameters for designing autostereoscopic imaging systems based on lenticular, parallax barrier, and integral photography plates - Son, JY; Saveljiev, VV; Choi, YJ; Bahn, JE; Kim, SK; Choi, HH (SPIE-INT SOCIETY OPTICAL ENGINEERING, 2003)
In designing an autostereoscopic imaging system based on either a lenticular, parallax barrier, or integral photography (IP) plate, geometrical parameters relating the viewing zone and image display panel combined with the plate are the first things to be determined for the system. To define parameters such as the size of the panel, multiview image arrangement, pitch and focal length of the plate, viewing zone distance from the panel, and others, an optical configuration composed of an image mask aligned in front of a point light source array is used. With this configuration, the geometrical parameters are calculated and their relationships are found. In addition, the concept of pixel cells is introduced to arrange multiview images in the display panel for full parallax image generation. (C) 2003 Society of Photo-Optical Instrumentation Engineers.